1993
DOI: 10.1210/jcem.76.6.8501150
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical assessment of bone formation and resorption in acromegaly.

Abstract: The effects of chronic GH and insulin-like growth factor-I (IGF-I) excess on bone metabolism were examined by measuring serum markers of bone formation and urine markers of bone resorption as well as vertebral bone densities in patients with active acromegaly. Fasting serum GH levels were elevated in all 27 patients (31 +/- 11 micrograms/L). Serum calcium levels were within the normal range, except in 3 of 27 (10%) patients with mild hypercalcemia. Urinary calcium excretion, however, was increased in 6 (22%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 39 publications
4
70
1
1
Order By: Relevance
“…Serum total calcium level is generally within the upper normal range and hypercalciuria is frequent in acromegalics [12][13][14]: this is due to the increased intestinal calcium absorption secondary to enhanced renal synthesis of 1,25 (OH) 2 vit D [4,8,15,16], although the increased bone resorption may contribute [3]. Furthermore, acromegalic patients show increased renal phosphate reabsorption [17] resulting in serum phosphate levels within or above normal range [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum total calcium level is generally within the upper normal range and hypercalciuria is frequent in acromegalics [12][13][14]: this is due to the increased intestinal calcium absorption secondary to enhanced renal synthesis of 1,25 (OH) 2 vit D [4,8,15,16], although the increased bone resorption may contribute [3]. Furthermore, acromegalic patients show increased renal phosphate reabsorption [17] resulting in serum phosphate levels within or above normal range [18].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acromegalic patients show increased renal phosphate reabsorption [17] resulting in serum phosphate levels within or above normal range [18]. Increased serum osteocalcin levels have been found in acromegalics [3,5,12,[19][20][21][22] as GH, IGF-I and 1,25 (OH) 2 vit D stimulate osteocalcin synthesis [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of bone resorption, the carboxyterminal telopeptide of type I collagen (ICTP) is excreted through collagen degradation, and this excretion rate is considered a parameter of the rate of bone degradation [13]. The measurement of serum PICP and ICTP levels has been reported to be useful in evaluating bone metabolism in various diseases [14][15][16][17].…”
Section: Procollagen (Picp) Is Cleaved From Procollagen Moleculesmentioning
confidence: 99%
“…Another original observation of our study was concerned with bone metabolism markers and their association with fractures. Previous studies demonstrated that active acromegaly was associated with increased calcium and phosphate serum levels, increased calciuria and markers of bone formation, and bone resorption (26,27,28,29,30,31). Bonadonna et al (14) found that fractured acromegalic women had higher serum bone alkaline phosphatase and urinary deoxypiridinoline and lower serum levels of vitamin D compared with non-fractured patients, but the study population was too small (36 women) to draw any real final conclusion.…”
Section: European Journal Of Endocrinologymentioning
confidence: 94%